Do Cash Holdings Impact the Financials of Companies? Evidence from India - Riyazahmed, K.; Sriram, M. (Indian Journal of Finance, 2024)
Purpose : The purpose of the study was to examine the impact of cash holdings on financial performance metrics, such as return on assets and Tobin’s Q. Further, the study analyzed the impact of external shocks like the global pandemic, in addition to various determinants of cash holdings. Design/Methodology/Approach : The study examined the financials of 38 non-financial firms listed On the National Stock Exchange’s broader market index, Nifty, for eight years from 2014 to 2021. Panel data regression methods like fixed effects, random effects, pooled OLS, and GMM were used in the analysis. Findings : The study found that cash holdings significantly affected the financial performance of companies measured by ROA but not on Tobin’s Q. Further, the global pandemic did not impact cash holdings. Also, financially unconstrained companies held more cash than financially constrained companies. Further, free cash flow, age, and capital expenditure determined cash holdings. However, dividend payment, working capital, and leverage did not show any significant impact. Results of the GMM validated the dynamic nature of cash holdings, and Indian companies took 3 years to adjust their cash holding position. Practical Implications : The study would help managers understand how factors, particularly external shocks like the global pandemic, affected firms’ cash holdings. It would also assist managers in determining the optimal cash-holding ratio of total assets to enhance a company’s value. Originality/Value : The study’s findings provided new evidence of the relationship between cash holdings and financial performance. Further, the study examined the impact of the pandemic on the cash-holding positions of Indian companies. It estimated the time taken by Indian companies to adjust the cash holdings during the phases of the pandemic.